System and method for determining and structuring of software requirements using domain ontology - A. Jabar, Marzanah; Ahmadi, Ramin; Shafazand, Mohammad Yaser; Abdul Ghani, Azim; Sidi, Fatimah; Hasan, Saadah; Yousefi, Niloofar (2014)
A method (200) for determining a plurality of requirements and structuring of the plurality of requirements during software development executed on a server (105) over a communicating network (113) includes the steps of receiving by a client device (115), at least one user defined requirement, retrieving the plurality of requirements from the at least one user by employing a retrieval platform, determining the plurality of requirements by extracting data by an extraction module (125) for extracting target elements from the plurality of requirements, structuring the target elements by classifying the target elements into categories, presenting the requirements in form of at least one formal and meaningful structure, and storing at least one formal and meaningful structure in a database (120).